The Relationship between microstructure and mechanical properties of strand Steel wires - Kisrane-Bouzidi, Ahmed; Zidani, Mosbah; Messaoudi, Salim; Abid, Tahar (University of Eloued جامعة الوادي, 2018)
In this research, the relationship between microstructure and mechanical properties of Steel strands containing a nearly fully pearlitic structure is investigated. strands Steel used for different engineering and industrial applications such as : hoisting loads, aerial cable-ways, the bridges decks, suspension cables, the retaining walls, the petroleum platforms, airports etc. because they offer a right combination of strength and ductility. They are composed of drawn steel wire twisted helicaly around an axial wire. These wires are obtained by the wiredrawing process of a hard perlitic steel wire of carbon concentration close to the eutectoid composition followed by a thermo-mechanical treatment of stabilization. The main goal of this work is to undertake a preliminary characteristic study of high-carbon steel wire rods intended for manufacture of strands. The two wires which are in a rough state of hot rolling are investigated by the following experimental techniques : Microstructure, Vickers microhardness, Tensile test and X-ray diffraction analysis.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Strand, High-carbon steel, Wire rod, Microhardness , X-Ray diffraction